Submarine Adventure stage 7 - Hunt, Rodrick (United Kingdom Oxford University Press, 2012)
This story begins at Wilf$1 (Bs birthday celebration. A mysterious gift box reveals a submarine, and the magic key glows$1 (Btransporting the children underwater to join Professor Tangle. They explore life beneath the waves, encountering fish and funny miscommunications with the Professor when he mishears things. In the end, the key glows again, returning them safely home.s
These books are part of the Oxford Reading Tree Level 7: Stories series, designed for children who are developing confidence and fluency in reading. The stories continue the popular adventures of Biff, Chip, Kipper, Wilf, and friends, combining everyday school life with imaginative journeys sparked by the magic key.